2017
DOI: 10.1111/caim.12250
|View full text |Cite
|
Sign up to set email alerts
|

Collective action problems in public sector innovation: A business model perspective

Abstract: We explore how the literature on business models can explain the outcomes of innovation attempts in the public sector. Our findings suggest that governments can access a well‐developed knowledge domain for a public sector area but have a weak ability to propagate its value for society. Drawing on the business model literature concerning interdependence and distributed agency, we illustrate how a collective action problem related to innovation may arise in the public sector. We illustrate this new category of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Effects on companies of crisis‐driven innovation in the medium‐ and long‐term lie beyond the scope of this paper, and thus remain unaddressed. Annual reports indicate that some companies integrated new product businesses regardless of the type of pivoting path (Table 1), but future research should clarify medium‐ and long‐term effects on pivoting companies’ business model(s) and financial results (Axelson et al, 2017; Seetharaman, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Effects on companies of crisis‐driven innovation in the medium‐ and long‐term lie beyond the scope of this paper, and thus remain unaddressed. Annual reports indicate that some companies integrated new product businesses regardless of the type of pivoting path (Table 1), but future research should clarify medium‐ and long‐term effects on pivoting companies’ business model(s) and financial results (Axelson et al, 2017; Seetharaman, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…With our contribution, we aim to provide insights into the decision-making and implementation process of innovation projects in UWM and related infrastructure systems. Following Axelson et al (2017) and , we suggest a business model (BM) perspective for this purpose. "Indeed, the business model perspective holds the potential to facilitate public actors in collective actions for innovating new solutions, their open economy, and value creation."…”
Section: Problemmentioning
confidence: 99%
“…(Parsons, 2006) Many recent literature reviews have confirmed that a business model construct that includes a full range of stakeholders in an interdependent activity system of a firm has not yet been applied to the public sector. (Axelson et al, 2017;and Osborne and Brown, 2013 as examples) The business model perspective seldom includes innovation into public organizations because there are two economic challenges related to state involvement in the economy. The first one is an incentive problem, the influence of the self-interested behaviour of voters, interest groups, politicians, and government officials.…”
Section: Introductionmentioning
confidence: 99%